The ultimate resource - Simon, Julian Lincoln, 1932-1998 (Princeton University Press, 1981)
Presents a strong counterargument to those arguing for limits on population growth and the using up of natural resources and food. Human resources driving the discovery of new natural resources are the core of Simon's expansionist theories. This book and those by Herman Kahn are important to have a balence presentation of expansionist with conserver views.